In Close Proximity: The Lipid Droplet Proteome and Crosstalk With the Endoplasmic Reticulum. (March 2018) - Bersuker, Kirill; Olzmann, James A.
Lipid droplets (LDs) are conserved, endoplasmic reticulum (ER)-derived organelles that act as a dynamic cellular repository for neutral lipids. Numerous studies have examined the composition of LD proteomes by using mass spectrometry to identify proteins present in biochemically isolated buoyant fractions that are enriched in LDs. Although many bona fide LD proteins were identified, high levels of non-LD proteins that contaminate buoyant fractions complicate the detection of true LD proteins. To overcome this problem, we recently developed a proximity-labeling proteomic method to define high-confidence LD proteomes. Moreover, employing this approach, we discovered that ER-associated degradation impacts the composition of LD proteomes by targeting select LD proteins for clearance by the 26S proteasome as they transit between the ER and LDs. These findings implicate the ER as a site of LD protein degradation and underscore the high degree of crosstalk between ER and LDs.